A multiple methods evaluation of a cognitive behavioural therapy group for people with learning disabilities and anxiety. (7th October 2020) - Giannaki, Rengina; Hewitt, Olivia
Accessible summary: Cognitive Behavioural Therapy (CBT) can help individuals with learning disabilities and anxiety. A group was run to help people to manage their anxiety and to feel better. At the end participants and their supporters fed back their experiences of the group and filled in questionnaires to measure their anxiety and psychological distress. The group seems to reduce people's anxiety. This report adds to a growing body of existing literature demonstrating some benefits of CBT for people with learning disabilities and anxiety. Abstract: Background: Existing studies show mixed results of the effectiveness of CBT for people with learning disabilities and anxiety. Method: A CBT group was run for people with learning disabilities and anxiety, who attended with a supporter. Qualitative interviews were conducted post‐group and analysed using thematic analysis. Standardised questionnaires measuring anxiety, psychological distress and overall functioning were administered at pre‐ and post‐group, and at follow‐up. Results: Participants' anxiety decreased overall post‐group, which remained largely at follow‐up. The group and the supporters' involvement was helpful. Both supporters and participants recalled coping strategies that were presented in the group. Three out of four participants found attending a group challenging initially. The supporters seem to have specific expectations about the impact of the group. Conclusions: The results of the study are consistent with the existing, growing body of evidence which supports the use of CBT for people with learning disabilities and anxiety.